Non-Conviction Based Asset Forfeiture as an Instrument for Recovering State Losses in Corruption Crimes in Indonesia - Orrisa Firsta Graviddita; Indung Wijayanto (Law Research Review Quarterly, 2025)
NCBAF as emerged as a strategic legal instrument for recovering state losses arising from corruption, particularly in jurisdictions where conviction-based mechanisms prove ineffective. In Indonesia, the recovery of assets obtained through corruption remains heavily dependent on final and binding criminal judgments, a requirement that often delays asset confiscation and creates opportunities for offenders to conceal, transfer, or dissipate illicit assets. This study examines the weaknesses of the existing asset forfeiture framework within the Indonesian legal system and analyzes the urgency of adopting NCBAF as an alternative mechanism for recovering state losses in corruption cases. Employing normative legal research, this study adopts statutory and conceptual approaches through an analysis of national legislation and relevant international standards, particularly the United Nations Convention against Corruption (UNCAC). The findings demonstrate that the current conviction-based asset forfeiture regime is inadequate to address situations in which perpetrators have fled, died, or transferred assets to third parties. NCBAF, which operates through an in rem approach and focuses on the illicit origin of assets rather than the criminal liability of individuals, offers significant potential to accelerate asset recovery and close existing legal loopholes. The study concludes that comprehensive and clearly formulated regulations governing NCBAF are urgently required to strengthen Indonesia’s anti-corruption framework, enhance the effectiveness of state loss recovery, and ensure legal certainty while upholding due process of law.